Tantangan Dalam Pengembangan Kreativitas Anak Usia Dini di TK Masjid Nurul Muslimin - Sinaga, Dinda Aulina; Anggraini, Elya Siska; Adriani, Karina Dinda; Nababan, Lindawati Elisabeth; Sinaga, Lisda (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research was carried out to examine the development of creativity in early childhood at the Nurul Muslimin Mosque Kindergarten. The research method used in this research is a qualitative method with a qualitative descriptive approach. The subjects in this research were teacher educators at the Nurul Muslimin Mosque Kindergarten. The data collection techniques used in this research are interviews, observation and documentation. Through observations and interviews, this research identified several obstacles in developing children's creativity, namely limited space for expression, differences in levels of self-confidence, and difficulties in working together. Several strategies are designed to overcome the identified barriers by providing a wide space for expression, varied media, fun and dynamic learning, encouraging social interaction, and eliminating the fear of mistakes. It is hoped that this research can contribute to the development of creativity in early childhood by providing practical and innovative solutions that are easy to implement.